Enhanced structural stability and overall conductivity of Li-rich layered oxide materials achieved by a dual electron/lithium-conducting coating strategy for high-performance lithium-ion batteries. Issue 41 (29th July 2019) - Gao, Dan; Zeng, Zhisen; Mi, Hongwei; Sun, Lingna; Ren, Xiangzhong; Zhang, Peixin; Li, Yongling
Abstract : A dual coating of LATP and CNTs accelerates the transportation of Li + and electrons, resulting in improved rate capability. Abstract : Li-rich layered oxides (LLOs) are successfully modified by a dual coating of superionic conductor Li1+ x Al x Ti2− x (PO4 )3 (LATP) and electronic conductor carbon nanotubes (CNTs). In comparison to common ionic and electronic insulator metal oxides, the dual coating of LATP and CNTs efficiently suppresses the structural transformation and side effects of LLOs reacting with electrolyte, and slows down the oxidative decomposition of electrolyte to moderate the reduction of discharge capacity and voltage. In addition, the overall conductivity of the composites is obviously increased due to the fast ion transport channels of LATP and the one-dimensional ion transport networks of CNTs, which can not only accelerate the transportation of Li +, but also speed up the electron migration, resulting in improved rate capability of the composites. The LLO@LATP@CNT sample exhibits optimal cycling performance with a stable discharge capacity of 192.4 mA h g −1 and merely 0.12 V voltage decay after 100 cycles at 0.2C. It also displays a good stability after 500 cycles at 1C with a capacity retention rate of 82.7%. AC impedance and DC polarization measurements indicate that the LLO@LATP@CNT sample possesses higher electronic conductivity (8.91 × 10 −8 S cm −1 ) and the highest ionic conductivity (1.93 × 10 −6 S cm −1 ) compared to its pristine counterparts.